2012
DOI: 10.1152/ajpendo.00458.2011
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone regulates smooth muscle contractile pathways in the rat prostate: emphasis on PDE5 signaling

Abstract: ) plays a permissive role in the development of benign prostatic hyperplasia (BPH), and phosphodiesterase 5 inhibitors (PDE5is) have been found to be effective for BPH and lower urinary tract symptoms (LUTS) in clinical trials. This study investigated the effect of T on smooth muscle (SM) contractile and regulatory signaling pathways, including PDE5 expression and functional activity in prostate in male rats (sham-operated, surgically castrated, and castrated with T supplementation). In vitro organ bath studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 74 publications
4
26
0
Order By: Relevance
“…In accordance with our previous studies , the surgically castrated rat model was validated by the significant weight loss of the androgen‐sensitive organs (prostate and seminal vesicle), which was recovered after T supplementation. Also in line with previous observations , the current study showed T deprivation‐produced ED which was confirmed by the dramatically attenuated ICP/MAP elicited by ES of the cavernous nerve of castrated rats.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our previous studies , the surgically castrated rat model was validated by the significant weight loss of the androgen‐sensitive organs (prostate and seminal vesicle), which was recovered after T supplementation. Also in line with previous observations , the current study showed T deprivation‐produced ED which was confirmed by the dramatically attenuated ICP/MAP elicited by ES of the cavernous nerve of castrated rats.…”
Section: Discussionsupporting
confidence: 93%
“…% viability = (OD of Test/OD of Control) ×100 [3] Lactate dehydrogenase assay Lactate dehydrogenase (LDH) assay is used as a quantitative marker enzyme for the intact cell, its activity providing information on cellular glycolytic capacity. Measurement of LDH release (leakage) is an important and frequently applied test for severe irreversible cell damage.…”
Section: Mtt Assaymentioning
confidence: 99%
“…6 Androgen deprivation has been shown to influence a1-adrenoceptors both in their densities and related prostate contractions. [7][8][9][10] Hormone changes caused by 5a-reductase inhibitors are different from those caused by androgen deprivation. Androgen deprivation can greatly decrease both testosterone and DHT levels, whereas 5a-reductase inhibitors can only decrease DHT levels but otherwise increase testosterone levels.…”
mentioning
confidence: 99%